PSVIII-22 Maternal vitamin and mineral supplementation affect fetal hepatic expression of genes underlying mineral homeostasis and lipid metabolism in early pregnancy. (8th October 2021) - da Silva Diniz, Wellison Jarles; Ward, Alison K K; Reynolds, Lawrence P P; Borowicz, Pawel P P; Sedivec, Kevin K K; McCarthy, Kacie L L; Kassetas, Cierrah J J; Baumgaertner, Friederike; Kirsch, James D; Dorsam, Sheri T T; Neville, Tammi L L; Forcherio, J Chris; et al.
Abstract: Vitamins and minerals play critical roles in functions such as hormone production, DNA synthesis, regulation of gene expression, and lipid metabolism. However, the impact of vitamin and mineral supplementation on fetal programming and the interplay with gene expression of fetal organs remains unclear. We used a differential gene expression analysis to determine effects of maternal vitamin and mineral supplementation (from pre-breeding to d 83 post-breeding) on fetal hepatic gene expression and the pathways underlying liver function and metabolism at 83 d of gestation. Crossbred Angus beef heifers were supplemented (VTM, n = 7) or not (CON, n = 8) with 113 gheifer -1 d -1 of mineral premix (Purina ® Wind & Rain Storm All-Season 7.5 Complete) from a minimum d 71 before breeding through d 83 of gestation. After breeding, heifers were fed to gain 0.79 kg/d. All heifers were surgically ovariohysterectomized on d 83 and fetal liver collected. Total RNA was isolated from the fetal liver (n = 15) and gene expression measured with RNA-Seq. After library quality control and read mapping, differential expression was performed using edgeR. We identified 53 genes upregulated and 37 downregulated in the VTM group (adj.Pval < 0.1). Genes involved with mineral homeostasis, such as MT1A, MT1E, and MT2A, were among those differentially expressed underlying the mineral absorption pathway. ABCA1 and ABCA6, which are involved in cholesterol and metal ion transport across the plasma membrane, and PPARG and SDR16C5, that act on lipoprotein transport and metabolism, were upregulated in the VTM group. Also upregulated in the VTM group, the CUBN gene plays a role in vitamin and iron metabolism. In summary, maternal vitamin and mineral supplementation from pre-breeding to d 83 of gestation leads to upregulation of fetal hepatic genes acting on mineral homeostasis, lipid transport, and metabolism.